Areas and Special Lines 2

Calculus Level 5

There are two lines which are both tangent and normal to the curve x = ( y + 1 ) 2 3 + 1 x = (y + 1)^{\frac{2}{3}} + 1 .

One of the tangents is tangent to the curve at B B and is normal to the curve at E E and the other tangent is tangent to the curve at C C and is normal to the curve at F F .

If the area A A bounded by the curve x = ( y + 1 ) 2 3 + 1 x = (y + 1)^{\frac{2}{3}} + 1 and the line segments B F BF and E C EC can be expressed as A = α α β α λ A = \dfrac{\alpha^{\alpha}\beta\sqrt{\alpha}}{\lambda} , where α , β \alpha,\beta and λ \lambda are coprime positive integers, find α + β + λ \alpha + \beta + \lambda .


The answer is 1228.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Oct 7, 2018

Let y = t 3 1 x = t 2 + 1 d y d x ( t = t 1 ) = 3 2 t 1 y = t^3 - 1 \implies x = t^2 + 1 \implies \dfrac{dy}{dx}|(t = t_{1}) = \dfrac{3}{2}t_{1} \implies the tangent line to the curve at ( x ( t 1 ) , y ( t 1 ) ) (x(t_{1}),y(t_{1})) is: y ( t 1 3 1 ) = 3 2 t 1 ( x ( t 1 2 + 1 ) ) y - (t_{1}^3 - 1) = \dfrac{3}{2}t_{1}(x - (t_{1}^2+ 1))

Let the line be normal to the curve at ( x ( t 2 ) , y ( t 2 ) ) ( t 2 t 1 ) ( t 2 2 + t 1 t 2 + t 1 2 ) = 3 2 t 1 ( t 2 t 1 ) ( t 2 + t 1 ) 1 2 ( t 2 t 1 ) ( 2 t 2 2 t 1 t 2 t 1 2 ) = 0 (x(t_{2}),y(t_{2})) \implies (t_{2} - t_{1})(t_{2}^2 + t_{1}t_{2} + t_{1}^2) = \dfrac{3}{2}t_{1}(t_{2} - t_{1})(t_{2} + t_{1}) \implies \dfrac{1}{2}(t_{2} - t_{1})(2t_{2}^2 - t_{1}t_{2} - t_{1}^2) = 0 t 1 t 2 t 2 = t 1 2 t_{1} \neq t_{2} \implies t_{2} = -\dfrac{t_{1}}{2}

Since the tangent is also normal to the curve at ( x ( t 2 ) , y ( t 2 ) ) 9 4 t 1 t 2 = 1 (x(t_{2}),y(t_{2})) \implies \dfrac{9}{4}t_{1}t_{2} = -1 9 8 t 1 2 = 1 t 1 = ± 2 2 3 \implies \dfrac{9}{8}t_{1}^2 = 1 \implies t_{1} = \pm\dfrac{2\sqrt{2}}{3} \implies the two slopes are ± 2 \pm\sqrt{2} .

B : ( 17 9 , 16 2 27 27 ) B:(\dfrac{17}{9},\dfrac{16\sqrt{2} - 27}{27})

F : ( 11 9 , 2 2 27 27 ) F: (\dfrac{11}{9}, \dfrac{2\sqrt{2} - 27}{27})

For the segment B F BF and the curve y = ( x 1 ) 3 2 1 y = (x - 1)^\frac{3}{2} - 1

m B F = 7 2 9 y = 63 2 x 71 2 81 81 m_{BF} = \dfrac{7\sqrt{2}}{9} \implies y = \dfrac{63\sqrt{2}x - 71\sqrt{2} - 81}{81} .

Let f ( x ) = 63 2 x 71 2 81 81 f(x) = \dfrac{63\sqrt{2}x - 71\sqrt{2} - 81}{81} and g ( x ) = ( x 1 ) 3 2 1 g(x) = (x - 1)^\frac{3}{2} - 1

By symmetry the area A = 2 11 9 17 9 f ( x ) g ( x ) d x = 2 11 9 17 9 7 9 2 x 71 2 81 ( x 1 ) 3 2 d x = A = 2\displaystyle\int_{\frac{11}{9}}^{\frac{17}{9}} f(x) - g(x) \:\ dx = 2\displaystyle\int_{\frac{11}{9}}^{\frac{17}{9}} \dfrac{7}{9}\sqrt{2}x - \dfrac{71\sqrt{2}}{81} - (x - 1)^{\dfrac{3}{2}} dx=

2 ( 7 2 18 x 2 71 2 81 x 2 5 ( x 1 ) 5 2 ) 11 9 17 9 = 44 2 1215 = α α β α λ = 2 2 11 2 1215 α + β + λ = 1228 2(\dfrac{7\sqrt{2}}{18}x^2 - \dfrac{71\sqrt{2}}{81}x - \dfrac{2}{5}(x - 1)^{\frac{5}{2}})|_{\frac{11}{9}}^{\frac{17}{9}} = \dfrac{44\sqrt{2}}{1215} = \dfrac{\alpha^{\alpha}\beta\sqrt{\alpha}}{\lambda} = \dfrac{2^2 * 11 * \sqrt{2}}{1215} \implies \alpha + \beta + \lambda= \boxed{1228}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...